Meningkatkan Kemampuan Mengenal Huruf dengan Menggunakan Flash Card pada Anak Sekolah Dasar di SD Negeri Wasur Merauke - Dina Mariana Tarigan (Medan Resource Center, 2022)
Language skills are a basic need for elementary school children to be able to communicate and socialize with each other. One of the most basic language skills is recognizing letters in order to enter the reading stage. This study aims to improve the ability of students to recognize letters, spell words, and recognize pictures. The method used in this research is to use a flash card. By using flash cards, the learning method will be more creative and not monotonous so that students will be more enthusiastic in the teaching and learning process. Flash card digunakan sebagai alat bantu agar anak mampu mengenal huruf, mengeja kata dan mengenal gambar. Dalam menganalisis data, peneliti menggunakan metode observasi dan wawancara. Observation method is used to analyze the ability of students during class research. While interviews are used to determine the development of each child during the research. This research was conducted at Wasur State Elementary School. The object of this research is the 1st grade elementary school students. The reason the researcher chooses the first grade elementary school students is because the first grade elementary school students aged around 7-8 years are children who have beginner language skills. so that researchers hope that with this research, grade 1 elementary school students at Wasur State Elementary School can improve their language skills, namely letter recognition, spelling words, and recognizing pictures.